Dinamika Kebijakan Pendidikan Di Pondok Pesantren dan Madrasah Diniyah - Ariarta, Aliffany Pualam; Latif, Muhammad Sabri; Zahroh, Fatimatuz; Suti’ah, Suti’ah; Aziz, Abdul (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This study is to examine and identify the development of government policies for education in pesantren and madrasah diniyah. Using qualitative research methods, with the type of library research. The results showed that Islamic boarding schools began to receive government attention after the enactment of Law No.20 of 2003 concerning the national education system, in which both institutions were recognized as religious education institutions. The position and existence of the institution became stronger after the enactment of Government Regulation No.55 of 2007 concerning religious and religious education. The implementation procedures have been listed in PMA Number 13 of 2014. Equalization continues to be pursued through changes in existing policies to make pesantren and madrasah diniyah equal to other educational institutions, including the rights that must be obtained from the state. In 2019, Law No. 18/2019 was passed which was specifically prepared as an education policy in pesantren, with the main points regarding the form of institutions, the objectives and functions of pesantren, funding sources, and education quality assurance systems.